Treatment with Cardiotonic Pills® after Ischemia‐Reperfusion Ameliorates Myocardial Fibrosis in Rats. (9th January 2013) - Wei, Xiao‐Hong; Liu, Yu‐Ying; Li, Quan; Yan, Li; Hu, Bai‐He; Pan, Chun‐Shui; Li, Zhi‐Xin; Chang, Xin; Fan, Jing‐Yu; Zhao, Na; Sun, Kai; Huang, Ping; et al.
Abstract Objective The present study was designed to evaluate whether CP was beneficial in alleviating myocardial fibrosis following I/R injury. Methods Sprague–Dawley rats were subjected to 30 minutes occlusion of the LADCA, followed by reperfusion. CP (0.4 or 0.8 g/kg) was daily administered starting from three hour after reperfusion until day 6. Coronary venular diameter, RBC velocity, albumin leakage, MBF, heart function, myocardial infarction and fibrosis size, myocardium ultrastructure, MPO activity, and MDA level were evaluated. The expression of MCP‐1, RP S19, TGF‐β1, P‐Smad3, Smad4, MMP‐9 and α‐SMA, and the infiltration of leukocytes were examined. Results CP post‐treatment ameliorated I/R‐induced myocardial RBC velocity reduction, MBF decrease, cardiac dysfunction, and albumin leakage increase. Moreover, myocardial infarction and fibrosis size, MPO activity, MDA level, the expression of RP S19, TGF‐β1, P‐Smad3, Smad4, MMP‐9 and α‐SMA, the number of CD68‐positive cells increased significantly after I/R, and myocardium collagen deposition was observed on day 6 after reperfusion. All the alterations after I/R were significantly ameliorated by CP. Conclusions Post‐treatment with CP ameliorates I/R‐induced myocardial fibrosis, suggesting that CP may be applied as an option for preventing cardiac remodeling after I/R injury.